An Acoustic Transponder System - Spiess, F. N.; Loughridge, Michael S.; McGehee, Maurice S.; Boegeman, D. E. (The International Hydrographic Review, 2015)
Acoustic transponders provide a particularly appropriate means for navigating relative to the deep sea floor. Their successful use, however, is dependent on solution of certain engineering problems and on understanding of the sound propagation situation in which the equipment is to be used. During the past year we have developed, built and used a set of appropriate, inexpensive transponders. These allow for selective calling of any one of three units (using pulses at 10.0, 10.5 or 11.0 kc) all of which reply at 12.0 kc. The design lifetime is 106 pulses delivered over a period of up to one year. They have been built primarily to provide tracking information for a deeply towed, unmanned vehicle used for echo sounding and magnetometer observations. With this system useful responses have been obtained to ranges of 8 nautical miles. In normal operation the useful range is limited by the shadow zone formed by upward refraction of the acoustic energy near the sea floor. Use at sea has shown that these elements can provide effective navigational information and has allowed direct observation of the shadowing effects as the principal range limiting factor.